Characterisation of recombinant 3CL protease from SARS-CoV-2 produced in E. coli BL21 (DE3) for screening anti-covid drug candidates using rhodamine 110-synthetic peptide conjugate as a substrate - Putra, Gede Eka Perdana; Ulfah, Maria; Hafizh, Naufal; Prabandari, Erwahyuni Endang; Firdayani,; Helianti, Is (Penerbit Universiti Kebangsaan Malaysia, 2023)
The prediction that the pandemic is progressing towards becoming endemic does not change the fact that COVID-19 can still be fatal for individuals with weak immune systems. Therefore, anti-COVID drugs are still needed, even when the disease becomes endemic. With regards to SARS-CoV-2, the roles of 3CL protease are crucial in the formation of new virus particles. Therefore, inhibiting the function of these viral proteases will directly prevent viral replication in the human body. In this study, we report the production of a recombinant 3CL protease from SARS-CoV-2 in E. coli BL21 (DE3), which has not been extensively studied in Indonesia. The purified 3CL protease exhibited high solubility and functional activity. Additionally, the recombinant enzyme was characterised using the Rhodamine 110 fluorogenic peptide substrate. We showed that the recombinant 3CL protease was unstable in the presence of a DMSO concentration above 10%. Using the Rhodamine 110 fluorogenic peptide substrate, we found that the enzyme had a KM of 47.0 µM, Vmax of 0.41 RFU/s, and kcat/KM of 0.0088 RFU/μM2 . s while the IC50 of the GC376 was 13.35 nM. We also tested three bioactive compounds (catechin, emodin, and 1,4-naphthoquinone) using this recombinant protease as a protein target, and 1,4-naphthoquinone was the most promising bioactive compound in inhibiting the SARS-CoV-2 virus.